Unveiling the Value Proposition : Real Estate Appraisers as Strategic Partners in Business Decision- Making - Ziyad Ibraheem Alzaidan (MultiTech Publisher, 2024)
This study investigates the pivotal role of real estate appraisers in strategic decision-making and value enhancement, paying special attention to the planning aspects often overlooked in existing literature. Despite an abundance of research on real estate valuation, many studies have predominantly focused on financial aspects, neglecting crucial planning dimensions. Additionally, with Saudi Arabia experiencing rapid growth in its real estate market and heightened competition among valuation companies. In response to these dynamics, the study employs a descriptive approach to examine literature reviews, aiming to bridge existing gaps by delving into the planning facets of real estate valuation. It particularly considers the establishment of the Saudi Authority for Accredited Valuers (TAQEEM) in early 2017, Through an insightful analysis, it underscores the multifaceted roles of appraisers in risk management, financial reporting, investment analysis, portfolio management, and market intelligence. Additionally, it explores the implications of technological integration in appraisal practices and offers actionable recommendations for maximizing appraiser contributions to business strategy.